Different genetic impact in the development of renal length and width: a twin study. Issue 1 (January 2015) - Tarnoki, D. L.; Tarnoki, A. D.; Bata, P.; Littvay, L.; Garami, Z.; Berczi, V.; Karlinger, K.
Abstract Background Ultrasound measurements of renal dimensions are conventionally limited to renal length, shape and cortical thickness. These are regarded as adequate for normal therapeutic decision‐making and volume measurements are reserved for a few clinical trials. However, there is no evidence concerning the degree to which renal length or volume is independently susceptible to heritable and environmental influences. Aim We aimed to determine whether renal length or width (as a surrogate of volume) was more influenced by heritability. Methods A single operator measured renal length and width in 114 adult monozygotic and same‐sex dizygotic Hungarian twin pairs (mean age 43.6 ± 16.3 years), using an Esaote MyLab 70X ultrasound machine with curved array transducer (1–8 MHz, CA431). Results Analysis of within‐pair co‐twin correlations adjusted for age and gender showed that the age‐ and sex‐adjusted heritability of average renal length was 51% (95% confidence interval, 29–72%). Renal width showed negligible genetic influence. Common environmental effects had no influence, and unshared environments were responsible for 49–80% of the variance, mainly renal width. Conclusions This study is the first to demonstrate the moderate heritability and limited environmental influence on renal length, and the contrasting lack of heritability of renal width, which is mainly influenced by unshared environmental components, that is lifestyle habits. Renal width therefore better represents the influence of modifiable environmental factors than renal length. The results suggest that renal width not length should be reported to facilitate early detection and monitoring of renal disease.